Designing and Building Business Models Using Microsoft Excel - Robson J. Andrew (Mcgraw Hill Book Company, 1995)
A formal and structured approach to building spreadsheet models for use in business-decision making. Preface, Introduction to Spreadsheet Modelling, Problem Conceptualization and Data Analysis, Designing a Formal Spreadsheet Model, Determining the Contents of a Formal Spreadsheet Model, Model Automation (An Introduction to Macros), Model Validation and Verification, Model Documentation, Using a Formal Model to Explore Different Business Scenarios, Additional Issues in Spreadsheet Modelling, Templates and Libraries of Code, Glossary of Terms, Index.